Party lines competition, partisanship, and congressional redistricting - Mann, Thomas E.; Cain, Bruce E. (Brookings Institution Press, 2005)
"Details the legal and political history of redistricting since the inception of one person-one vote, documenting its impact on competition, polarization, and partisan fairness, and analyzes options for reform"--Provided by publisher.